Postoperative Voiding Dysfunction: The Preferred Method for Catheterization. Issue 1 (January 2019) - McDermott, Colleen D.; Ryan, Victoria; Pulver, Ariel; Boutet, Marianne
Abstract : Objectives: Bladder drainage can be achieved by clean intermittent self-catheterization (CISC), transurethral indwelling catheterization (TIC), or with a suprapubic tube (SPT). The primary objective of this study was to determine patient preference for catheter type in the management of potential voiding dysfunction after pelvic organ prolapse (POP) surgery. Methods: Between 2012 and 2016, patients scheduled for POP surgery were recruited into the study. Before surgery, patients were informed of the potential for postoperative voiding dysfunction and the catheter choices were discussed. Each patient's choice was recorded along with baseline information, surgery performed, and perioperative details. After surgery, voiding dysfunction, length of catheter use, scores on a catheter satisfaction questionnaire, as well as uroflowmetry and urine culture testing were assessed. Results: Of those recruited to the study (N = 150), 6.7% chose CISC, 7.3% chose TIC, and 86% chose SPT. Catheter satisfaction score 1 week after surgery was significantly better for SPT compared with CISC and TIC ( P = 0.005). In addition, at week 1, 33% of CISC, 25% of TIC, and 13% of SPT had a PVR of more than 30% ( P = 0.002) on uroflowmetry, and 33% of CISC, 50% of TIC, and 24% of SPT had a positive urine culture ( P = 0.05). Conclusions: This study has shown that patients prefer SPT over CISC and TIC for management of voiding dysfunction after POP surgery. Use of SPT showed better satisfaction rates, better uroflowmetry results, and lower infection rates 1 week after surgery. Patient preference is an important factor in this decision and can help facilitate a clinical approach. Abstract : A suprapubic tube is preferred more than intermittent catheterization and indwelling catheter for management of voiding dysfunction after prolapse surgery.